Защита клиентов банков от мошенничества путём подмены номера - Найдёнова, Д. Р. (ХНУРЕ, 2020)
In the abstract, the situation with the growth of fraud in the banking sector due to a telephone number change is described. The technical side and the proper use of the Caller ID Customization function are reviewed. The negative implications of the Caller ID Customization function using by scammers are shown. Recommendations for banks and bank costumers for the fraud changing numbers protection are proposed.